Criptomoeda e Blockchain: o rigor das regras brasileiras frente ao mercado tradicional - Soares, Luciana de Paula (2021)
The objective of this dissertation is to analyze the Normative Instruction n 1.888/19 of the Federal Revenue of Brazil where it obliges all users located in Brazil and exchanges to send the transacted data. This obligation is compared to the legislation of the traditional exchange market, which is similar to the operations carried out in the crypt currency market. It is questioned the competence of the tax authorities to create rules for data collection without prior legal justification, in a context where the lack of specific rules and government guidelines has contributed to the institution's protagonism, which may lead to unauthorized data sharing, tax interpretations and future taxes. The thesis defends that cryptomaps should be considered as currency, with the Central Bank of Brazil being the federal agency with the competence and technical knowledge to legally regulate the matter and exercise effective control of this market that moves an astonishing financial volume. The methodology adopted was deductive and the present study used a qualitative approach.